The Incidence of Unnatural Death Before the COVID-19 Pandemic and During the COVID-19 Pandemic at the POLRI Hospital in East Jakarta in 2017-2021 Based on the Visum Et Repertum Results and The Review Ascording to the Islamic Perspective - Dela Riyanti; Ferryal Basbeth; Firman Arifandi (Junior Medical Journal, 2022)
Unnatural deaths are caused by homicide, suicide and accidents. The COVID-19 pandemic has triggered problems that have led to unnatural deaths. This study aims to determine the incidence of unnatural deaths before and during the COVID-19 pandemic. This study uses a descriptive method with a retrospective study design using medical record data from 620 victims. The population of this study were victims of unnatural deaths (2017-2021) who were examined at the East Jakarta POLRI Hospital according to inclusion criteria. The results showed that the frequency of unnatural deaths in homicides occurred the most before the COVID-19 pandemic in 2017 as many as 122 victims (29.97%) and the highest gender was male with 104 victims (25.55%) and the age range Most were 17-25 years old with 42 victims (10.32%). In the case of suicide, the most cases occurred during the COVID-19 pandemic in 2020 as many as 19 victims (32.76%) with the highest gender being male with 14 victims (24.13%) and the highest age range being 26-35 years as many as 6 victims (10.34%). In the case of traffic accidents, the most occurred before the COVID-19 pandemic in 2019 as many as 57 victims (36.77%) with the highest gender being male with 43 victims (27.74%) and the highest age range being 17-24. 25 years as many as 20 victims (12.91%). Most of the victims of unnatural death in homicide cases occurred before the COVID-19 pandemic with male gender and an age range of 17-25 years. In many cases of suicide occurred during the pandemic, with male gender and age range 26-35 years. Meanwhile, many traffic accident cases occurred before the pandemic, with male gender and an age range of 17-25 years.